2006
DOI: 10.1590/s1413-86702006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Response to treatment with interferon-alpha and ribavirin in patients with chronic Hepatitis C virus genotypes 2 and 3 depends on the degree of hepatic fibrosis

Abstract: The combined therapy with interferon alfa plus ribavirin (INF+RBV) is considered the most appropriate treatment for patients with chronic hepatitis C virus genotypes 2 and 3 in Brazil. However, wide variations in the rates of sustained viral response (SVR) have been reported among such patients. We evaluated, retrospectively, factors associated with SVR in subjects with chronic hepatitis C virus genotypes 2 and 3 and that received medication from the Health Secretariat of the state of São Paulo. One-hundred-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…5,6,13,14 in Brazil, previous studies in patients with genotype 2 or 3 treated with biosimilar standard ifn plus RBV showed SVR rates ranging from 39 to 46%, similar to that found in the present study. [15][16][17] on the other hand, one Brazilian study on patients with genotypes 2 or 3 infections who were treated with Peg-ifn plus RBV found a SVR rate of 67%. 18 Biosimilar standard ifn plus RBV treatment is routinely used in Brazilian patients with genotype 2 or 3 infections and, according the present study findings, it was less effective regarding SVR than what would be expected according to the literature.…”
Section: Characteristicmentioning
confidence: 99%
“…5,6,13,14 in Brazil, previous studies in patients with genotype 2 or 3 treated with biosimilar standard ifn plus RBV showed SVR rates ranging from 39 to 46%, similar to that found in the present study. [15][16][17] on the other hand, one Brazilian study on patients with genotypes 2 or 3 infections who were treated with Peg-ifn plus RBV found a SVR rate of 67%. 18 Biosimilar standard ifn plus RBV treatment is routinely used in Brazilian patients with genotype 2 or 3 infections and, according the present study findings, it was less effective regarding SVR than what would be expected according to the literature.…”
Section: Characteristicmentioning
confidence: 99%
“…This leads to liver cirrhosis and, ultimately, to liver carcinoma ( 4 ). Although numerous therapeutic options are currently available for liver fibrosis, all have limited degrees of success and none were capable of producing a complete cure ( 5 ). Thus, there is an urgent need to develop better preventative options as well as treatment approaches, based on a more thorough understanding of the pathogenesis of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, patients with advanced stage fibrosis had low rates of response to this combined therapy, and a criterion of treatment with pegylated interferon as a first alternative should be considered (Parise et al, 2006). Despite this considerations we don't do sub analysis considering the degree of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…SVR rates in individual studies in Brasil to Non-HIV naïve patients with HCV genotype 2 or 3 who underwent treatment with IFN plus RBV for 24 weeks varied from 33% to 80% (Alves, De Azevedo et al, 2003;Acras, Pedroso et al, 2004;Borges, 2004;Villela-Nogueira, Perez et al, 2005;Parise, De Oliveira et al, 2006;Fachini, 2008;Almeida et al, 2009;Carneiro et al, 2010;Vigani et al, 2012). SVR rates from this Brazilian studies are very different from each other and below the main clinical trials found in literature (Manns et al, 2001).…”
Section: Discussionmentioning
confidence: 99%